EDUKASI KESEHATAN SEBAGAI UPAYA PENCEGAHAN KEJADIAN HIPERTENSI PADA USIA PRODUKTIF DI SMA SARASWATI 1 DENPASAR - Lestari, Yuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Abstract: The problem of hypertension is a health challenge not only in Indonesia but almost throughout the world. The productive age group experienced an increase in the incidence of hypertension by 4.5% in the 15-24 year age group and 14.7% in the 25-34 year age group. The tendency to increase the prevalence of hypertension in the productive age group is caused by unhealthy lifestyles such as lack of physical activity, poor diet, smoking habits and drinking alcohol. One effort that can be made to control hypertension rates is to provide education from an early age about implementing a healthy lifestyle using the CERDIK method, especially in the adolescent age group. This activity aims to increase teenagers' knowledge about efforts to prevent hypertension in productive age. This community service method is by providing health education and measuring the level of knowledge before and after the education using questionnaires. The results of this activity were that before the counseling was given, 14 people (44%) had a poor level of knowledge, 10 people (31%) had a sufficient level of knowledge and 8 people (25%) had a good level of knowledge. After being given counseling, it was found that 24 people (75%) had a good level of knowledge, 8 people (25%) had a sufficient level of knowledge and no one had poor knowledge. Through outreach, it is hoped that knowledge can be increased so that it can change attitudes and behavior for the better in an effort to prevent the incidence of hypertension in the productive age. Key words: hypertension, health education, intelligence, knowledge